Evaluation of muscle injuries in professional football players: Does coach replacement affect the injury rate? - Dönmez, G.; Kudas, S.; Yörübulut, M.; Yildirim, M.; Babayeva, N.; Torgutalp, S.; Seyma L. (Clinical Journal of Sport Medicine, 2020)
Objectives: To assess the incidence and characteristics of muscle injuries in professional football players and to assess if coach dismissal may be related with muscle injuries within 1-month period from the dismissal. Design: Prospective cohort study during 3 consecutive seasons. Setting: Turkish Super League football teams. Participants: One hundred eighteen male football players. Main Outcome Measures: Data on time-loss muscle injuries confirmed using magnetic resonance imaging were recorded, including type, body part, duration, and lay-off time, and training session and match exposure times. The muscle injury rate was evaluated at 2 weeks and 30 days after coach dismissal. Results: In total, 124 muscle injuries were recorded, with injury incidences of 2.3 muscle injuries per 1000 hours of exposure overall, 1.2 in training sessions, and 13.6 in matches. Injury time loss ranged from 3 to 67 days (median, 13 days). Eighteen percent of the injuries (n = 23) were recurrent; no association was found between recurrence rate and the player's age or position (P = 0.15, P = 0.27, respectively). Recurrent injuries caused more severe injuries (26.1%, P = 0.02) and longer median lay-off time (P = 0.01). During the study, teams A and B replaced 7 and 3 coaches, respectively. The injury incidence increased to 5.3 per 1000 hours of exposure in the 2 weeks after the coach dismissal, and decreased to 4.5 within 1 month of coach dismissal. Conclusion: Given the link between coach dismissal and increased rates of muscle strain injuries, increased attentiveness to preventing muscle injuries during coaching transitions and to the impact of new training regimens is required by trainers and medical teams.